Effect of Varied Concentrations of Ethylhene Glycol as Pooled Serum Preservative on the Stability of Alkaline Phosphatase (ALP) Ezyme - Fitri Fadhilah; Sandra A. Riyadi; Euis Yuliani (Future Science)
Quality controls aim to ensure the quality, accuracy, and thoroughness of an examination. Internal quality assurance is carried out by the laboratory itself using control materials, both commercial control materials and homemade control materials. This controlled material is then used to ensure the quality of an inspection. The stability of the control material is strongly influenced by the storage temperature where the recommended temperature is -20? which will be stable for up to 6 months and 2-8? which is stable for 6 days. In the manufacture of homemade control materials, a stable preservative, antifreeze, and antibacterial is needed but still maintains the integrity of the group serum. The preservative used is ethylene glycol. This study aims to determine the optimal concentration of ethylene glycol in stabilizing alkaline phosphatase levels in refrigerator temperature storage (4-8ºC) for 60 days. In this study, tests were conducted on pooled sera preserved with ethylene glycol in varying concentrations, namely 7.5%; 10%; 12.5%; 15%; and 17.5% and observed the stability of the Alkaline Phosphatase enzyme in pooled sera for 60 days with an interval of 10 days with a storage temperature of 4-8?. The study was conducted in July-August 2021 in the BLUD laboratory of RSUD dr. Ben Mboi, Manggarai. The results showed that the stability of alkaline phosphatase persisted until day 30, began to decrease on day 40, and continued to decrease until day 60 in each different concentration variation. different, namely 7.5%; 10%; 12.5%; 15%; and 17.5% had the same stability up to 30 days. The recommendation from the author is to observe at different temperatures so that the stability of Alkaline phosphatase can be known.